Pengaruh Karakteristik Peserta Didik terhadap Hasil Belajar di Sekolah Dasar - Riswanda Riswanda (Universitas Sebelas Maret, 2020)
One of the obstacles in teaching and learning activities in schools is the characteristics of students. Recognizing the characteristics of students is something that needs to be done by an educator. One of the cases that occurs in learning is the low interest in learning of students. This is a case that often occurs in learning at school. The Covid-19 pandemic has created new habits. Now almost everyone who is familiar with the gadgets used to be brave with its various applications, poses a dilemma: it is very useful on one side and dangerous on the other. Useful because all things starting from school children, doing homework, collecting assignments. Dangerous because it can cause addiction to children. Results Based on the literature review, the characteristics of students are: ethnicity, culture, social status, interests, cognitive development, prior knowledge, learning styles, motivation, emotional development, moral development, spiritual development and motor development. Constraints in general in learning activities, namely motivation and interest in learning.